Effect of Trunk Stabilization Exercises on Static and Dynamic Sitting Balance among Children with Cerebral Palsy: A Randomized Control Trial - Faiqa Mehmood Rana, Saima Jabbar, Maham Khalid, Sana Umar, Mehboob Ali, Uzra Batool, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the effectiveness of trunk stabilization exercises on Static and Dynamic Sitting Balance among Children with Cerebral Palsy Method: This randomized controlled trail was conducted at physiotherapy department, Mayo hospital, Lahore. 38 children were with cerebral palsy were enrolled in this study via non-probability purposive sampling technique which later on randomized and allocated to two equal groups. Group A received specific core stability training while group B received conventional physical therapy treatment. Written informed consent was procured from every participant or their guardian through signed consent forms. Questionnaire used for data collection was Gross Motor Function Measure (GMFM-88) also used for assessment of sitting balance. Results: Descriptive statistics showed participants were having mean age of6.00 ±2.00 for group A and 5.52±.1.80 for Group B. Participants who received trunk stabilization exercises showed marked improvement as compared to group B. There was a statistically significant improvement in all measured variables following the intervention (P<0.05). Pre-treatment sitting GMFM mean score in group A was 27.54 ± 3.61, while in group B was 26.48 ± 4.64. After 3 week treatment mean score in group A was 30.04 ± 3.81 and in group B was 27.43 ± 4.36 and post treatment mean score in group A was 32.80 ± 3.54 and in group B was 29.46 ±4.36. Practical Implication: This research would lay another evidence highlighting the effectiveness of trunk stability exercises to not only improve sitting balance among cerebral palsy patients but also the quality of life among them. Conclusion: It was concluded from the study that trunk stabilization exercises showed significant improvement in static and dynamic sitting balance scale among cerebral palsy children. The children when treated with trunk stabilization exercises showed a significant treatment outcome when analyzed on Gross Motor Function Measure GMFM-88. Keywords: Cerebral Palsy, Trunk control, Static sitting Balance, Dynamic sitting balance, GMFM-88.